RAY TRACING ALGORITHM FOR 3D SCENE RENDERING - Tārauds, Valdis; Meirāns, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
In this work, authors implemented simple gpu ray tracing algorithm, that can render image with realistic reflections. To achieve result author use Unity as main development tool.